Breeding origins and migratory connectivity at a northern roost of Vaux's Swift, a declining aerial insectivore. (7th August 2019) - Smith, Ellis L; Reudink, Matthew W; Marra, Peter P; Mckellar, Ann E; Van Wilgenburg, Steven L
ABSTRACT: Populations of Vaux's Swift ( Chaetura vauxi ), like those of many aerial insectivores, are rapidly declining. Determining when and where populations are limited across the annual cycle is important for their conservation. Establishing the linkages between wintering and breeding sites and the strength of the connections between them is a necessary first step. In this study, we analyzed 3 stable isotopes (δ 13 C, δ 15 N, δ 2 H) from feathers collected during spring migration from Vaux's Swifts that perished during a stopover on Vancouver Island, British Columbia, Canada. We previously analyzed claw tissue (grown during winter) from the same individuals, revealing that the swifts likely wintered in 2 or 3 locations/habitats. Here, we used stable isotope analysis of flight feathers presumed to have been grown on, or near, the breeding grounds to determine the likely previous breeding locations and presumed destinations for the swifts. Stable isotope values (δ 13 C, δ 15 N, δ 2 H) showed no meaningful variation between age classes, sexes, or with body size. Surprisingly, ~26% of the birds sampled had feather isotope values that were not consistent with growth on their breeding grounds. For the remaining birds, assigned breeding origins appeared most consistent with molt origins on Vancouver Island. Overall, migratory connectivity of this population was relatively weak ( r M = 0.07). However, the degree of connectivity depended on how many winter clusters were analyzed; the 2-cluster solution suggested no significant connectivity, but the 3-cluster solution suggested weak connectivity. It is still unclear whether low migratory connectivity observed for Vaux's Swift and other aerial insectivores may make their populations more or less vulnerable to habitat loss; therefore, further efforts should be directed to assessing whether aerial insectivores may be habitat limited throughout the annual cycle.